Advanced supercritical fluid technique to reduce amorphous silicon defects in heterojunction solar cells. (1st August 2022) - Chou, Sheng-Yao; Lin, Shih-Kai; Chang, Ting-Chang; Tsai, Tsung-Ming; Huang, Jen-Wei; Chen, Shih-Wei; Shen, Chang-Hong; Shieh, Jia-Min; Lin, Chao-Cheng; Yang, Chih-Cheng
Abstract: The advanced supercritical fluid (SCF) technique was applied to reduce defects in the amorphous silicon thin-film layer and enhance the efficiency of a heterojunction (HJT) solar cell from 18.1% to 19.6%. An amorphous silicon thin-film layer has been used as a passivation layer between the substrate and electrode contact in HJT solar cells; however, many dangling bonds exist in the amorphous silicon thin-film layer. Therefore, the SCF technique was developed to passivate defects. The advantage of a supercritical state is high penetrability and low temperature. Thus, this SCF treatment can passivate defects in the completed device without changing the original fabrication process. After treatment, the passivation of dangling bonds was examined using Fourier-transform infrared spectroscopy, which confirmed the improved Si–H bonding. Moreover, electrical properties such as open-circuit voltage, short-circuit density, efficiency, shunt resistance, and leakage current were measured to confirm the enhancement. A simulated light source of 1 kW M −2 global AM1.5 spectrum was used to analyze the increase in cell efficiency, and the dark current was analyzed to confirm the leakage current improvement. Finally, a model for explaining the phenomenon in cells after treatment was developed.